Remarks on the existence and uniqueness of periodic solution for nth-order functional differential equations with infinite delay - Afonso, S. M. [UNESP]; Furtado, A. L. (My University, 2018)
In this work we apply the coincidence degree theory to establish a result on the existence and uniqueness of periodic solution for a class of nth-order functional differential equations with infinite delay. An example is given to illustrate our result.
Keywords: Coincidence degree; Existence; Functional differential equations; Infinite delay; Periodic solution; Uniqueness